Maritime endangered archaeology of the Middle East and North Africa: the MarEA project. (December 2020) - Andreou, Georgia; Blue, Lucy; Breen, Colin; El Safadi, Crystal; Huigens, Harmen Otto; Nikolaus, Julia; Ortiz-Vazquez, Rodrigo; Westley, Kieran
Abstract: Abstract : The 'Maritime Endangered Archaeology' (MarEA) project is conducting remote, large-scale identification and assessment of vulnerable maritime heritage to assist in its management in the face of challenges such as climate change and rapid urbanisation.